Revision of Amphiduros Hartman, 1959 (Polychaeta, Hesionidae, Gyptini) - Pleijel, F. (Ophelia, 2001)
A revision is presented of the taxonomy of Amphiduros Hartman, 1959 based on re-examined types, newly collected topotypes, and other specimens. Amphiduros axialensis Blake & Hilbig, 1990 is referred to Amphiduropsis, new genus. Amphiduros fuscescens (Marenzeller, 1875), A. Izukai Hessle, 1925, A. Pacificus Hartman, 1961 and A. Selosus Hessle, 1925 cannot be conclusively diagnosed, wherefore the three latter are synonymised with A. Fuscescens. Amphiduros fuscescens is newly recorded from Papua New Guinea and the Great Barrier Reef; the taxon appears to have a circumtropical and warm-water temperate distribution. Following a parsimony analysis based on morphological characters, Amphiduros and Amphiduropsis constitute a monophyletic group, either with Gyptis Marion & Bobretzky in Marion, 1874, or part of Gyptis, as sister taxon. In parallel to the traditional Linnean nomenclature, I present an alternative phylogenetic nomenclature of the group, with apomorphy-based definitions of taxon names and without recognition of any Linnean ranks (including species).
World Polychaeta Database (WPolyDb)